Proposal for an approach to evaluate continuity in service supply chains: Case of the Moroccan electricity supply chain - Houda Mezouar; Abdellatif El Afia (International Journal of Electrical and Computer Engineering (IJECE), 2019)
The purpose of this paper is to develop an approach to analyse and evaluate continuity in Service Supply Chain (SSC), through a case study. This approach is based on the data-driven quality strategy "Define, Measure, Analyze, Improve, Control" (DMAIC) which is used to drive Six Sigma projects, and on the characteristics of Smart Supply Chain. It combines Business process management (BPM), Supply Chain Operations Reference (SCOR), and the Root cause analysis tree diagram. The chosen case study is the electricity SCC, especially the business process 'management of electricity for residential buildings' of the Moroccan electricity SSC. The paper shows that the suggested approach identifies the discontinuity causes for the studied SSC, improves the business process behavior and manages its control by providing a dashboard that encompasses KPIs for periodically controlling of the SSC "to-be" state.